Kegiatan sosialisasi dalam upaya pencegahan pernikahan dini di Desa Sidang Muara Jaya, Kecamatan Rawa Jitu Utara, Kabupaten Mesuji - Kurniati, Erlin; Farizal, Ahmad; Artiarani, Artiarani; Eldiyan, Eldiyan; Amanda, Firda Dhea Dwi; Ramadhan, M. Dimas; Adilla, Senza Putra; Puspita, Violla Dwi (Nur Science Institute, 2024)
This Community Service Program aims to reduce the rate of early marriage, which is implemented through collaboration between KKN UIN Raden Intan Lampung students and Village officials and the community of Sidang Muara Jaya Village, North Rawajitu District, Mesuji Regency, Lampung Province. This program focuses on the importance of reducing the number of early marriages, especially for children under the age of 19, which is a significant problem in Sidang Muara Jaya Village. Factors that support the high rate of early marriages are identified as part of the program planning. This service is implemented through a socialization approach to increase public awareness of the negative impacts of early marriage and reduce the number of early marriages in each hamlet. This program also supports economic, social, and cultural maintenance. As a result, the community began to realize the importance of maintaining environmental cleanliness and supporting the work programs of KKN students in the village.